THE DEVELOPMENT OF MARKETING STRATEGY FOR PROMOTING THE POTENTIAL BUSINESS COMMUNITY: A CASE STUDY OF COTTON HAND WEAVING PRODUCTS GROUPS AT CHIANG RAI VILLAGE, NAN PROVINCE - ปั้นรูป จิตรา; พลเยี่ยม ดวงสมร; กันธิยะ อภิญญา; ชินบุตร วรรณิดา; เขียวคำอ้าย ณัฏฐณิชา; จารุศุกร์ รัชชา; ดวงใจ เอกชัย (RMUTT Global Business and Economics Review, 2017)
The study on “The development of marketing strategy for promoting the potential business community, case study: the cotton hand weaving products groups at chiang rai village, Nan province” was conducted by using samples comprised 23 person. The instrument was a rating scale questionnaire (in part 1) and interview (in part 2), to obtain the data were analyzed by means, standard deviation, and percentage. The results were presented in two parts of study as follows: Part one was explanted on general information of farmer who produced the cotton hand weaving products in the Chiang Rai village. The result shows that most of the farmers were females (95%) aged between 51 to 60 years old (43%) with married status (100%). Most of them were primary education (65%) and the average monthly income between 5,000 to 10,000 Baht/Month (100%). The popular product were pa-sin (fabric xian) (31.94%) and pa-hom (blankets) (27.78%), respectively. The business and commercial of the cotton hand weaving production in each farmer were conducted manufacturers and wholesalers with themselves. Part two was explained on general information about the marketing environment of the cotton hand weaving products in the Chiang Rai village. The result shows that this production were reduced due to increasing of competitor in the part of the cotton hand weaving production as well as current economic situation in thailand. For marketing environment include strengths, weaknesses, opportunities and threats of the cotton hand weaving products, The result shows that the cotton hand weaving products had strengths such as sponsored by the academy in the area, skilled workers and local knowledge while the weaknesses of goods were depended on imported raw materials, lack of modern technology, designer, as well as knowledge skill. For marketing strategy of the cotton hand weaving products at the current, the result shows that the marketing effectiveness of farmer are still needing help from the main target market, Phufa Pattana Center. In this study, the result found that the development of a marketing strategy as follows: 1) should develop a model of the product, a unique group and distinguished. 2) Product price should be set at a higher price to allow consumers to compare with other product. 3) product distribution should also add a variety of distribution channels that customers can easily access.